A Finite Difference Time Domain Investigation of Electric Field Enhancements Along Ocean‐Continent Boundaries During Space Weather Events. Issue 6 (5th June 2018) - Pokhrel, Santosh; Nguyen, Bach; Rodriguez, Miguel; Bernabeu, Emanuel; Simpson, Jamesina J.
Abstract: Geomagnetic disturbances caused by solar storms have the potential to create large‐scale geomagnetically induced currents in long conductors at the Earth's surface. These may disrupt the operation of electric power grids and cause blackouts. Ocean‐continent boundary regions are of particular concern because of the sharp contrast between the higher ocean electrical conductivity compared to the lower continental conductivity. This contrast may generate high‐amplitude geoelectric fields and cause power grids in coastal regions to be more vulnerable to space weather hazards. Previously, analytical calculations were used to estimate geomagnetically induced currents at ocean‐continent boundaries. However, for the analytical equations to be solvable, the physics and geometries of the problem were simplified. As a result of these simplifications and due to a lack of published measurements examining this issue in coastal regions, it is difficult to know for sure whether there are unique hazards to electric power grids at ocean‐continent boundaries. In this paper, a grid‐based, time domain modeling approach is used to solve the complete Maxwell's equations, which permits accommodation of (1) the complete physics of the propagating electromagnetic fields from disturbed ionospheric currents through the air and into the lithosphere and even into the ocean via the skin effect and (2) more realistic coastal geometries. Using this more robust approach, in the variety of scenarios studied in this paper, only a local enhancement of the electric fields was observed, which are expected to only pose potential hazards to power grids only a local scale near ocean‐continent boundaries. Key Points: Electromagnetic fields across ocean‐continent boundaries are solved via FDTD while accounting for a finite‐depth ocean and topography Analytical approaches are found to provide a close approximation to the more realistic FDTD results for the range of studied scenarios Surface electric field enhancements are highly localized along the coast, even for low frequencies and shallow oceans